DEVELOPING LOCAL-FOLKLORE INSTRUCTIONAL READING MATERIALS FOR EIGHTH GRADERS - Mariana, Dina (University of Sriwijaya, 2017)
Abstract: This study aimed at finding out the validity, practicality, and potential effect of the developed instructional reading materials using local folklores from Muara Enim Regency for the eighth graders. The procedure of the study consisted of three stages: analysis, design, and evaluation. In evaluation stage, a set of formative evaluations consisting of self evaluation, experts review, one-to-one, small group, field test was conducted. There were two experts reviewing the product in the expert review stage, three students involved in one-to-one evaluation, nine students involved in small group evaluation, and thirty students of a real class involved in field test. The data were obtained from questionnaires and test. The obtained data were analyzed by using average score for the questionnaires and percentage for the test. The findings showed that the developed product was valid in terms of its content and instructional design with the average score 3.52 (very highly valid). The developed reading materials were practical after being evaluated in one-to-one evaluation with the average score 3.19 (highly practical) and small group evaluation with the average score 3.7 (very highly practical). Then, the product also had high potential effect after being evaluated in field test as 73.3% of students passed the minimum mastery criterion. It can be said that the developed product are potentially effective to be applied for the target students.